INCREASING FEED EFFICIENCY AND SPECIFIC GROWTH OF AFRICAN CATFISH (Clarias gariepinus) WITH PAPAYA LEAF EXTRACT SUPPLEMENTATION - Huda J., Mhd. Aidil; Nisari, Tika; Rumondang, Anne; Batubara, Helfinasyam; Suriyadin, Adi; Aulia, Nurul (Universitas Mataram, 2025)
Papaya leaf extract is known to have various benefits, including the papain enzyme which can function as a protein digester and improve the fish's immune system. The use of natural ingredients such as papaya leaf extract can also reduce dependence on synthetic chemicals, making it safer for human health and the environment. Based on the explanation above, it is necessary to conduct research on the effect of giving different doses of papaya leaf extract on the specific growth rate, feed conversion ratio and also the water quality of African catfish (Clarias gariepinus) seeds. This research was conducted in June - August 2024 at the Fisheries Production Laboratory of the Matauli Fisheries and Marine College. The effect of adding papaya leaf extract to feed with different doses on the specific growth rate, feed conversion ratio and water quality of African catfish (Clarias gariepinus) seeds produced the best results. The best treatment for Specific Growth Rate was in the P1 treatment of 1.405%, Feed Conversion Ratio of 1.411, and water quality in the form of temperature and pH which were in optimal conditions. This dose can be an alternative as a natural ingredient that has benefits to support an environmentally friendly and sustainable catfish (Clarias gariepinus) seed cultivation system.